Cost analysis of a modular rocket engine architecture - Liu, Shangyu (2018)
This report deals with the development progress of the methodology to investigate and analyze the potential cost savings of a modular rocket engine architecture inspired by Falcon 9, SpaceX, adopting the nine-engine architecture on the first stage. Modular design has been widely documented in literature and implemented in industry as an effective approach for company to minimize product cost and improve operation efficiency. However, there are few practical models in the field of rocket engine R&D and even less to elaborate how those cost benefits are derived. Through this report, a relatively comprehensive framework is aimed to be developed for the relevant companies and institutes to use as guideline to evaluate the modular design methodology and analyze potential cost benefits from it. The investigations are focused on the potential cost savings information which are related to the Falcon 9 rocket engine architecture. The discussions are mainly focused on cost elements and their effects on the total cost whereas limitations and further research scopes are also indicated. A mathematical model was established, and numerical analysis was also implemented within the MATLAB for further the comparison and analysis under the real case study. With this model, companies involved should be able to get a clear picture and hence to make a more informed decision when comparing modular rocket engine architecture against traditional architectures. Keywords: Cost, Modular, Rocket Engine Architecture.